2021
DOI: 10.1016/j.conb.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The social network: Neural control of sex differences in reproductive behaviors, motivation, and response to social isolation

Abstract: Social animal species present a vast repertoire of social interactions when encountering conspecifics. Reproduction-related behaviors, such as mating, parental care, and aggression, are some of the most rewarding types of social interactions and are also the most sexually dimorphic ones. This review focuses on rodent species and summarizes recent advances in neuroscience research that link sexually dimorphic reproductive behaviors to sexual dimorphism in their underlying neuronal circuits. Specifically, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 217 publications
(335 reference statements)
1
13
0
Order By: Relevance
“…These findings are well in line with previous knowledge from pairwise behavioral assays in which females engage in more social interactions and find them more rewarding. 88 , 89 , 90 , 91 Our current results extend these past findings into the context of a group and show that sex differences in social motivation, including greater sociability in females, are maintained in complex social structures under naturalistic settings. Similarly, extensive sex differences in the dynamics and behavioral strategies undertaken to form hierarchies were also found in other mammalian species, including hyenas, 87 , 92 foxes, 93 rhesus monkeys, 94 baboons, 95 , 96 and even humans.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are well in line with previous knowledge from pairwise behavioral assays in which females engage in more social interactions and find them more rewarding. 88 , 89 , 90 , 91 Our current results extend these past findings into the context of a group and show that sex differences in social motivation, including greater sociability in females, are maintained in complex social structures under naturalistic settings. Similarly, extensive sex differences in the dynamics and behavioral strategies undertaken to form hierarchies were also found in other mammalian species, including hyenas, 87 , 92 foxes, 93 rhesus monkeys, 94 baboons, 95 , 96 and even humans.…”
Section: Discussionsupporting
confidence: 84%
“…It is also likely to be involved in the control of instinctive behaviors in humans. 3 Social sensory inputs are known to reach the cerebral cortex via the thalamus; however, it is not known how information needed for social behavior arrives in the hypothalamus.…”
Section: In Briefmentioning
confidence: 99%
“…Transcriptomic and epigenomic characterization of BNST ERα-expressing neurons revealed that sexual differentiation does not constrain the capacity to mount a genomic response to estradiol in adulthood. Likewise, manipulation of hormone levels, chemosensory input, or neuronal activity causes both sexes to engage in behaviors typical of the opposite sex, once considered "sexspecific" (Wei et al 2021;Zilkha et al 2021). These findings converge upon a model of behavioral sex differences as probabilistic rather than absolute: perinatal estradiol establishes differential gating or thresholding of shared neural circuitry, providing quantitative variation in behavioral intensity as opposed to qualitative presence or absence of hard-wired behaviors.…”
Section: Concluding Remarks: a Spectrum Of Sex Differencesmentioning
confidence: 99%